Optimasi Penerapan Algoritma Yolo dan Data Augmentasi dalam Klasifikasi Pakaian Tradisional Kebaya - Mulyana, Dadang Iskandar; Sahroni (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
Kebaya is one of Indonesia's traditional clothes which has a long history and is rich in culture. Each region or tribe in Indonesia has a kebaya with its own characteristics, including unique patterns, colors and decorations .Indonesian society want to know the kebaya from their area of origin but have difficulty distinguishing the kebayas because there are only slight differences in certain parts of the kebaya which are characteristic of kebaya from one area with kebaya from other regions. Therefore we need a system that can detect or classify traditional kebaya clothes in Indonesia. Researchers use the YOLOv8 version in making this system. The YOLOv8 algorithm goes through a classification system for kebaya clothes, processes such as annotation, preprocessing, augmentation, training to testing. The research results show good results with a confidence value of 90% - 97%. The final results of testing on 12 images show the output by knowing the kebaya class and good accuracy and producing an average accuracy value of 94%.